Pelatihan Penyusunan Kurikulum Operasional Madrasah (KOM) dan Program Kerja Madrasah - Khasanah, Niswatul (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2025)
This community service program was motivated by the fact that many madrasahs still face difficulties in developing the Madrasah Operational Curriculum (KOM) in line with the Independent Curriculum framework. The main objective was to improve teachers’ competence in designing a contextual and applicable KOM and annual work program in accordance with the latest regulations. The method employed was Participatory Action Research (PAR) through a collaborative workshop involving 22 teachers and education staff of MI Al-Kifayah Pekanbaru. Data were collected through observation, interviews, and document analysis, and were analyzed using a descriptive qualitative approach. The results indicated a significant improvement in teachers’ understanding, from 70% who had limited knowledge at the beginning to 90% who felt confident in curriculum design after the training. All participants attended the three-day workshop actively, producing a complete KOM document for the 2025/2026 academic year, an integrated annual work program, and an internal curriculum development team. These findings confirm that the PAR-based approach effectively enhanced teachers’ capacities and strengthened participatory-based madrasah governance. The program implies greater institutional independence in curriculum management, improvement of teachers’ digital literacy, and the potential replication of this mentoring model in other madrasahs.